2021
DOI: 10.1371/journal.pone.0255412
|View full text |Cite
|
Sign up to set email alerts
|

A seroprevalence survey of anti-SARS-CoV-2 antibodies among individuals 18 years of age or older living in a vulnerable region of the city of São Paulo, Brazil

Abstract: A second wave of COVID-19 has demonstrated how challenging it will be to achieve sustained control of the disease, even with vaccination underway in many countries. Therefore, it remains relevant to keep improving our understanding of the distribution of COVID-19, especially of asymptomatic individuals, among different populations, and particularly in vulnerable regions. Hence, this population-based serosurvey had the objective of estimating the prevalence of individuals 18 years of age or older infected by SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“… 40 In a vulnerable area in Sao Paulo city (Paraisópolis), a 43·8% prevalence was found among individuals aged 18 years or older ( n = 272) (from September to December 2020). 41 Moreover, a prospective cohort study conducted in the same neighbourhood as our study estimated the incidence of COVID-19 during four waves (from May 2020 to Nov 2021) and found that the incidence was much higher than previously reported by similar studies in the US and that the incidence was the highest in the first wave (May through November 2020). 42 These results suggest that the burden of COVID-19 is highly unequal, impacting to a much higher degree vulnerable and marginalized populations.…”
Section: Discussionsupporting
confidence: 49%
“… 40 In a vulnerable area in Sao Paulo city (Paraisópolis), a 43·8% prevalence was found among individuals aged 18 years or older ( n = 272) (from September to December 2020). 41 Moreover, a prospective cohort study conducted in the same neighbourhood as our study estimated the incidence of COVID-19 during four waves (from May 2020 to Nov 2021) and found that the incidence was much higher than previously reported by similar studies in the US and that the incidence was the highest in the first wave (May through November 2020). 42 These results suggest that the burden of COVID-19 is highly unequal, impacting to a much higher degree vulnerable and marginalized populations.…”
Section: Discussionsupporting
confidence: 49%
“…In another study in a large university clinic in the region, using the same RDT, 13.9% of 439 outpatients July 2020 tested positive 14 . An evaluation using the ECLIA assay on vulnerable populations of the metropolitan area, showed higher rates, 43.8% (95% CI: 37.7-50%) 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies estimated the proportion of infected individuals in South America after the large Gamma and Lambda epidemics in 2021, but some evidence from seroprevalence data support our estimations. A randomized study conducted in Paraguay between March to June 2021 gave a seroprevalence of 23.1% in Asunción and of 26.9% in the central region of the country 30 and a recent seroprevalence survey among adult individuals living in the largest Brazilian city of Sao Paulo also estimate a high proportion (45%: 39-51%) of individuals infected by SARS-CoV-2 31 .…”
Section: Discussionmentioning
confidence: 99%